Studying and comparison of health literacy among smokers and non-smokers students in Shahid Beheshti University of Medical Sciences in 2016 - Rahman Panahi; Ali Ramezankhani; Mahmoud Tavousi; Aliasghar HaeriMehrizi; Fereshte Osmani; Shamsaddin Niknami (Mashhad University of Medical Sciences, 2018)
Background and objective: The relation of low health literacy with negative health consequences such as less adopting of preventive behaviors, premature death and weaker state of health has been proven. Due to the increase of using smoking among students, this study was performed with the purpose of determining and comparing health literacy among smoker and non-smoker students. Methods: This research is the cross-sectional study among dormitory students of Shahid Beheshti University of Medical Sciences in Tehran was performed. The sample size of 360 people has been included by single-stage random cluster sampling. The data collection tools were demographic information and health literacy questionnaire (HELIA). Data were analyzed using descriptive statistics and t-test in SPSS (ver.16). Results: 59.1% (n=201) were studied non-smoker students, 17.1% (n=58) had experienced smoking and 23.8% (n=81) were current smokers. The mean and standard deviation of health literacy score were 70.52±14.12 from 100. The dimensions of understanding and access to the highest mean score, and then the decision making and application of health information had the lowest mean score. There was a significant difference between the mean of health literacy in two groups of smoker and non-smoker students. Also, there was a significant difference between the mean scores of the dimensions of understanding, decision making and application of health information and access in two groups of smoker and non-smoker students (P